Neurologic Clinical Signs in Cattle With Astrovirus‐Associated Encephalitis. (22nd May 2017) - Deiss, R.; Selimovic‐Hamza, S.; Seuberlich, T.; Meylan, M.
Abstract : Background: Evidence of neurotropic astroviruses has been established using novel genetic methods in cattle suffering from viral encephalitis of previously unknown origin. Objectives: To describe the clinical signs observed in cattle with astrovirus‐associated encephalitis. Animals: Eight cattle (4 cows, 3 heifers, and 1 bull of 4 different breeds) admitted to the Clinic for Ruminants for neurologic disease and 1 cow investigated in the field. Methods: Cases were selected based on neuropathologic diagnosis of nonsuppurative encephalitis, positive in situ hybridization result for astrovirus, and availability of the results of physical and neurologic evaluations. Laboratory results were evaluated if available. Results: The most frequently observed clinical signs were decreased awareness of surroundings (7), cranial nerve dysfunction (5), and recumbency (5). The cow seen in the field was the only animal that had severe behavioral changes. Cell counts in cerebrospinal fluid (CSF) were increased in 4 animals, and protein concentration was increased in 3 of 5 specimens. In 1 case, the presence of astrovirus could be identified in a CSF sample by reverse transcriptase polymerase chain reaction. Other laboratory abnormalities were nonspecific. Conclusions and Clinical Importance: Astrovirus infection may be an important differential diagnosis in cattle with clinical signs of brain disease and should be considered after exclusion of other causes. The clinical and epidemiological relevance of encephalitis associated with astrovirus infection should be further investigated.